Induction of Epitope-Specific Neutralizing Antibodies against West Nile Virus - Oliphant, Theodore (American Society for Microbiology (ASM), 2007)
Previous studies have established that an epitope on the lateral ridge of domain III (DIII-lr) of West Nile virus (WNV) envelope (E) protein is recognized by strongly neutralizing type-specific antibodies. In contrast, an epitope against the fusion loop in domain II (DII-fl) is recognized by flavivirus cross-reactive antibodies with less neutralizing potential. Using gain- and loss-of-function E proteins and wild-type and variant WNV reporter virus particles, we evaluated the expression pattern and activity of antibodies against the DIII-lr and DII-fl epitopes in mouse and human serum after WNV infection. In mice, immunoglobulin M (IgM) antibodies to the DIII-lr epitope were detected at low levels at day 6 after infection. However, compared to IgG responses against other epitopes in DI and DII, which were readily detected at day 8, the development of IgG against DIII-lr epitope was delayed and did not appear consistently until day 15. This late time point is notable since almost all death after WNV infection in mice occurs by day 12. Nonetheless, at later time points, DIII-lr antibodies accumulated and comprised a significant fraction of the DIII-specific IgG response. In sera from infected humans, DIII-lr antibodies were detected at low levels and did not correlate with clinical outcome. In contrast, antibodies to the DII-fl were detected in all human serum samples and encompassed a significant percentage of the anti-E protein response. Our experiments suggest that the highly neutralizing DIII-lr IgG antibodies have little significant role in primary infection and that the antibody response of humans may be skewed toward the induction of cross-reactive, less-neutralizing antibodies.